A contrastive-stylistic study into the tense distribution in English and Slovene fictional texts - Silvana Orel Kos (Linguistica, 2008)
The article addresses contrastive and narratological issues of the unity vs. diversity of temporal spheres in fictional texts. It focuses on the presentation of mimetic discourse within the past time-sphere narrative, trying to establish the narrative or stylistic functions of the present and past time-sphere verb actions with respect to the role of the narrator or that of the character. the diegetic and mimetic functions of verb actions in certain temporal spheres, ie. tense usage in (free) indirect discourse (free) direct discourse, will be contrastively studied in original fictional texts and their translations, in both directions between english and Slovene. the character’s mimetic discourse may be presented through different narrative forms, spanning the report-control cline from the forms “in total control” of the character, ie. free direct discourse, to that “apparently in total control” of the narrator, ie. speech act and thought act report (cf. Leech and Short 1981: 324). in addition to the character’s verbal and mental responses, the study includes mediated instances of the character’s sensory responses, the basic formula thus being: He said that/thought that/saw that. Our contrastive analysis considers only fictional texts whose diegesis is rendered   in the narrative past tenses, as the english language system observes the sequence of tenses, while the Slovene language does not. the diegesis of a fictional text may be completely located in the present time-sphere, yet such texts do not present any major issues in terms of contrastive relevance for the studied language pair.